On the Feasibility of Stereotactic Radiosurgery With 5.0 and 10.0 mm MLC Leaves as a Function of Target Size and Shape - Jalbout, Wassim; Abou Zahr, Jana; Youssef, Bassem; Shahine, Bilal (Frontiers in Oncology, 2019)
Introduction: This study explores the feasibility of SRS/SRT treatment with MLC leaves wider than 2.5mm at isocenter by inter-comparing treatment plans produced with 2.5, 5.0 and 10.0 mm leaves for various target sizes and shapes. Materials and Methods: Forty previously treated patients were re-planned using 2.5, 5.0 and 10.0 mm wide MLC leaves. For each patient, all three plans were evaluated and contrasted between them in terms of five metrics: target dose homogeneity, conformity index, organs at risk dose, dose fall off outside the target and dose to normal tissues. A regularity index RI was introduced that quantifies the degree of target shape irregularity. The effect of target size and shape irregularity on feasibility of 5.0 and 10.0 mm leaves was analyzed. Results: Consistent plan degradation was observed for 10.0 mm (sometimes for 5.0 mm) compared to 2.5 mm MLC in terms of the above five plan metrics, but this degradation was small to clinically insignificant. As an exception, when target (PTV) size was smaller than about 1 cm diameter, clinically significant differences were found between 2.5, 5.0 and 10.0 mm MLC. Conclusion: 5.0 and 10.0 mm MLC can be used in SRS/SRT for targets (PTV) diameter larger than 1 cm. For smaller targets, 2.5 mm MLC is clinically superior, 5.0 is acceptable and 10.0 mm MLC is discouraged in terms of PTV dose conformity.